PENGARUH EDUKASI MEDIA LEAFLET TERHADAP PENGETAHUAN DAN SIKAP MASYARAKAT PENGGUNA OBAT TRADISIONAL DI PETANJUNGAN PEMALANG - Munisih, Siti (Parapemikir : Jurnal Ilmiah Farmasi, 2025)
Knowledge and attitudes are included in the predisposing factors that influence behavior in using traditional medicine. Providing information through the media can increase public knowledge, one of which is leaflet media.The purpose of this research is to determine the characteristics and the influence of providing education through leaflet media on the knowledge and attitudes of the community regarding the use of traditional medicine. This descriptive research used a cross-sectional method. The sampling techniques employed were purposive and accidental sampling. Data analysis was conducted using the Wilcoxon test. The results of this study indicate that the sociodemographic characteristics of the community include respondents aged adults (18-44) with the majority being female (47.5%), predominantly homemakers (44.4%) for occupation, the majority having completed high school education (48.5%), and the majority having a monthly income of ≤ 2,500,000 (70.7%). After statistical analysis, a p-value of 0.001 (p0.05) was obtained for knowledge level and a p-value of 0.001 (p0.05) for attitude.